Influence of sanctions on the external trade of Russia - Alves, Oxana Nikolaevna Lykova (2021)
The impact of the sanctions imposed by the Western countries on Russia since March 2014, given their influence on the economy of Russia and other countries, has been the subject of much interest and discussion. The sanctions have an impact on international trade, economic stability and relationship between the countries. This thesis estimates the influence of sanctions on the economy of Russia resorting to multiple regression analysis. I find that, although, the sanctions affected heavily the Russian economy, the relationship between the explanatory variables in Russian exports and imports did not change due to the sanctions. I also find compelling statistical evidence that the external trade of Russia strongly depends on the Brent oil price. Diagnostic tests exhibit quite good model fits.